National survey on workplace safety and prevention services: regional differences - Martini, Agnese; Bonafede, Michela; Buresti, Giuliana; Bertazzi, Pier Alberto; Di Leone, Giorgio; Isolani, Lucia; Corso, Luca; Iavicoli, Sergio (La Medicina del Lavoro, 2016)
Background: Occupational Safety and Health (OSH) Services, with inspections and support activities to workers and to enterprises, have a relevant role in the field of safety and health in the workplace. Objectives: The aim of this study, part of the INSuLa Project, is to realize a national survey about risk perception of OSH and awareness about OSH issues in the context of the Italian OSH legislative framework (Legislative Decree 81/08 and subsequent modifications and integrations) implementation, with involvement of the OSH Services operators. Methods: The Survey involved a representative national sample of the OSH Services operators. After an analysis of background literature and a comparison with Operating Units involved in the Project, an ad hoc questionnaire was developed and administered to the sample to evaluate the topics of the Survey. Results: The study has been conducted on a sample of 678 OSH Services operators. The Survey showed in Italy an important organizational and procedural inhomogeneity perceived by OSH Services operators. Conclusions: This study highlighted the relevance perceived by OSH Services operators to develop a system of safety culture dissemination to reduce accidents at work and improve the management of occupational risks (traditional and emerging).